Health Benefits And Potential Risk Of Tropical Herbs From The Leguminosae Family: A Review - Mohd Rahman Omar; Hana Maizuliana Solehan; Fatin Afifah Rosli; Abdul Aziz Marwan; Ummu Aiman Faisal; Hilmi Lockman; Ahmad Najib Azmi (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2024)
Introduction: Tropical herbs are used as a medicine long before the introduction of modern medicine, especially by traditional healers. However, its’ scientific benefits are not widely investigated. There is a belief that the use of traditional herbs potentially causing health deterioration due to its unknown mechanism of actions and interactions, and the nature of its unregulated processing as a health supplement. Parkia speciosa (local: petai) and Pithecellobium jiringa (local: jering) are two tropical herbs from the Leguminosae family that are widely used raw as salads with many perceived health benefits and harms. We reviewed both species, looking into scientific pieces of evidence supporting the belief. Methods: The databases of MEDLINE, PubMed, EBSCOhost, and Google Scholars were systematically searched for both in vitro and in vivo effects of both species with no language restriction. Data were extracted using standardised fashioned. Results: P speciosa has pharmacological properties including antioxidant and anti-inflammation. It has shown to have antibacterial properties and glucose-lowering activity. P jiringa contains known antioxidant metabolites such as flavonoids, phenolics and terpenoids. It also contains antiangiogenic properties with potential use in retinopathy, cancer, and Rheumatoid arthritis. However, both herbs have potentially harmful effects which include liver injuries. Large consumption of P jiringa leads to acute kidney injury. Conclusion: Consumption of both P speciosa and P jiringa has medicinal properties as well as health harm. If taken as a supplement, rigorous clinical trials are needed to delineate benefit vs harm effect of both herbs.